A manganese hydride molecular sieve for practical hydrogen storage under ambient conditions. Issue 5 (19th December 2018) - Morris, Leah; Hales, James J.; Trudeau, Michel L.; Georgiev, Peter; Embs, Jan Peter; Eckert, Juergen; Kaltsoyannis, Nikolas; Antonelli, David M.
Abstract : An amorphous manganese hydride molecular sieve that reversibly absorbs 10.5 wt% and 197 kgH2 m −3 hydrogen at room temperature using the Kubas interaction. Abstract : A viable hydrogen economy has thus far been hampered by the lack of an inexpensive and convenient hydrogen storage solution meeting all requirements, especially in the areas of long hauls and delivery infrastructure. Current approaches require high pressure and/or complex heat management systems to achieve acceptable storage densities. Herein we present a manganese hydride molecular sieve that can be readily synthesized from inexpensive precursors and demonstrates a reversible excess adsorption performance of 10.5 wt% and 197 kgH2 m −3 at 120 bar at ambient temperature with no loss of activity after 54 cycles. Inelastic neutron scattering and computational studies confirm Kubas binding as the principal mechanism. The thermodynamically neutral adsorption process allows for a simple system without the need for heat management using moderate pressure as a toggle. A storage material with these properties will allow the DOE system targets for storage and delivery to be achieved, providing a practical alternative to incumbents such as 700 bar systems, which generally provide volumetric storage values of 40 kgH2 m −3 or less, while retaining advantages over batteries such as fill time and energy density. Reasonable estimates for production costs and loss of performance due to system implementation project total energy storage costs roughly 5 times cheaper than those for 700 bar tanks, potentially opening doors for increased adoption of hydrogen as an energy vector.